Multiphysics design optimization of RF-MEMS switch using response surface methodology. (January 2018) - Younis, Sadia; Saleem, Muhammad Mubasher; Zubair, Muhammad; Tahir Zaidi, Syed Muhammad
Abstract: This paper presents the multi-objective geometric design exploration and optimization of an electrostatic Symmetric Toggle RF-MEMS switch (STS), considering both the electromechanical and RF characteristics simultaneously. The output responses considered for the STS switch optimization are pull-in voltage, switching time, insertion loss in the on-state and isolation in the off-state. Metamodels for the output responses, with respect to geometric design parameters, are developed using Design of Experiments (DOE) based Response Surface Methodology (RSM) and Finite Element Method (FEM) simulations. A single optimization objective function, considering all the four output responses and microfabrication process constraints, is defined and optimized for the design factors using combined desirability function and heuristic search algorithm approach. The predicted values of the output responses are verified through both the electromechanical and electromagnetic FEM simulations. The effect of residual stress, developed in the RF-MEMS switch during the sacrificial layer removal step of the microfabrication process, on both the electromechanical and RF characteristics of the final optimized switch geometry is analyzed using coupled structural-thermal-electric FEM simulations. The proposed DOE and RSM based design optimization technique can be implemented for the design space exploration and optimization of complex MEMS devices which involve coupled multiphysics interactions.